2022
DOI: 10.1111/ijfs.15617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycation on protein structure, amino acid composition and digestibility of silver carp mince

Abstract: This study was to investigate the effects of glycation on the quality of silver carp mince (SCM) proteins. The browning index (BI), sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), Fourier transform infrared spectroscopy (FTIR), total amino acid composition, chemical score, protein digestibility and reductive power of digested products were determined. The correlation between the degree of glycation, protein structure and protein nutritional quality was analysed. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As can be seen in Table 3, the amino acid content increased as the surimi content increased from 10% to 40%, which was consistent with the study of others. 38 It was also found that the most abundant amino acids were Glu (190.05–222.38 mg per g protein), Asp (110.72–120.92 mg per g protein) and Leu (75.10–89.69 mg per g protein). However, the scarcest amino acids were Cys (7.76–9.00 mg per g protein), Trp (9.77–11.20 mg per g protein) and Met (11.49–16.33 mg per g protein).…”
Section: Resultsmentioning
confidence: 93%
“…As can be seen in Table 3, the amino acid content increased as the surimi content increased from 10% to 40%, which was consistent with the study of others. 38 It was also found that the most abundant amino acids were Glu (190.05–222.38 mg per g protein), Asp (110.72–120.92 mg per g protein) and Leu (75.10–89.69 mg per g protein). However, the scarcest amino acids were Cys (7.76–9.00 mg per g protein), Trp (9.77–11.20 mg per g protein) and Met (11.49–16.33 mg per g protein).…”
Section: Resultsmentioning
confidence: 93%
“…This discoloration could stem from the formation of aldehydes or carbonyl compounds due to lipid oxidation during processing. These compounds may interact with protein amino groups via the Maillard reaction, resulting in the production of colored reaction products. Alternatively, myoglobin may cross-link with MPs, leading to increased myoglobin formation and reduced whiteness of fish MPs .…”
Section: Relationships Between Actin and Food Qualitymentioning
confidence: 99%
“…The results showed that glycation could effectively improve the smell, taste, and texture of silver carp sausage, and enhance the overall acceptability of the product without changing the protein digestibility ( Liu, Huang, Feng, Luo, & Shi, 2022 ). In addition, we also investigated the changes in protein structure, protein nutritional value, glycation site, and volatile compounds of silver carp mince under different heating times with and without glucose ( Liu, Hu, Wei, & Shi, 2022 ; Liu, Shen, Xiao, Jiang, & Shi, 2022 ). Based on the above studies, we found that different reducing sugars (L-arabinose and glucose) may have different effects on the odor characteristics of silver carp mince, which may be related to the degree of glycation, which could be regulated by the type of reducing sugar.…”
Section: Introductionmentioning
confidence: 99%